Kegiatan Pembelajaran Kreatif Guru Di Masa Pandemi Covid 19 Untuk Meningkatkan Minat Belajar Siswa Pada Mi Ma’arif NU Rabak - Hidayatun, Umi; B.S., Abdul Wachid (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The research was conducted with the aim of describing the creative learning activities of teachers during the COVID-19 pandemic at MI Ma'arif NU Rabak. This research uses descriptive qualitative method. The analysis technique used is data reduction technique, data presentation and conclusion. The result of the research is that teachers' creative learning activities during the pandemic can increase children's interest in learning. Teachers can create creative learning using online learning. This learning can attract students' interest in learning, so students do not feel bored. With teacher guidance in online learning, of course, it can foster student learning enthusiasm. Using continuous greetings through class groups, the teacher seems to be in front of students in teaching and learning activities, therefore students feel happy and as an increase in student learning enthusiasm